Analysis of agglutinants elicited by antiserum of channel catfish immunized with extracellular proteins of virulent Aeromonas hydrophila. Issue 86 (March 2019) - Zhang, Dunhua; Xu, De-Hai; Beck, Benjamin
Abstract: Motile Aeromonas septicemia (MAS), caused by new virulent Aeromonas hydrophila (vAh) strains, has been one of the major diseases in channel catfish in recent years. Previous studies showed that channel catfish developed immunity against vAh infection after immunization with the pathogen's extracellular proteins (ECP). To understand the mechanisms associated with the immunity, anti-ECP fish serum (antiserum) was analyzed in this study. Our results revealed that the antiserum elicited agglutination of both ECP and cells of vAh. Five fish proteins were identified in ECP agglutinants, including two innate immunity associated proteins (serotransferrin and rhamnose-binding lectin), two immunoglobulin M (IgM) molecules (IgM heavy chain and light chain) and a constitutively-produced protein (warm temperature acclimation protein). More than 68 vAh proteins in ECP were recognized and caused to aggregate by IgM in the antiserum. IgM was isolated from vAh cell agglutinants and the native IgM was shown to form a tetramer that was responsible for bacterial agglutination. Immunoblotting analysis indicated that the isolated native IgM was able to recognize some proteins in ECP, such as aerolysin and hemolysin (in the form of a high molecular weight heterologous polymer). Gene expression analysis by quantitative PCR showed that fish immunized with vAh ECP had more transcripts of genes coding for IgM, serotransferrin and rhamnose binding lectin than mock-immunized fish. Both innate and antibody-mediated immune responses in serum and expressed genes contributed to fish immunity upon immunization with ECP. Results of this study shed light on the versatility of vAh antigens and catfish IgM, which would help identify specific antigens for vaccine development and antigen specific antibodies in catfish. Highlights: Immunization with extracellular proteins (ECP) of virulent Aeromonas hydrophila (vAh) provides channel catfish with immunity Anti-ECP serum elicited agglutination of both ECP and cells of vAh. Analysis of agglutinants revealed the diversity and versatility of IgM in the anti-ECP serum. Both innate and antibody-mediated immune responses in serum and expressed genes contributed to fish immunity.